New diagnostic methods for Escherichia marmotae and the first report of its identification in clinical isolates in North America - Oladipo, Pelumi M.; Tibbetts, Robert J.; Sivertsen, Audun; Barger, Justin M.; Bruvold, Torbjørn S.; Fite, Alemu; Sims, Matthew; Zervos, Marcus; Jomaa, Ali; Ram, Jeffrey L. (Frontiers in Microbiology, 2025)
BackgroundGenomic sequences of E. marmotae and E. coli differ by 10%. Discovered as an environmental “cryptic clade” of Escherichia, E. marmotae also occurs in human infections. Microbiological and MALDI-TOF-MS methods frequently misidentify E. marmotae as E.coli. Our goal was to develop methods that reliably distinguish E. marmotae from E. coli to improve therapeutic decisions and treatments.MethodsA Taqman PCR method was developed to distinguish E. marmotae from E. coli based on genomic sequences of uidA, uidB, and a positive control targeting adk in E. marmotae and E. coli. MALDI-TOF-MS spectra were obtained for environmental and clinical isolates using a bioMérieux VITEK MALDI-TOF-MS system.ResultsUidA- and uidB species-specific PCR amplified DNA from E. marmotae with 100% specificity, and not from E. coli or other Escherichia species. The Biomérieux VITEK MALDI-TOF-MS consistently misidentified E. marmotae as E. coli, with median IVD confidence scores for both E. marmotae and E. coli of 99.9%; however, RUO scores for E. marmotae (median 0%) were significantly lower (P < 0.0001) than for E. coli (median = 87.4%). The spectral peak between m/z 7,250 to 7,280 consistently occurred between 7,260 and 7,268 in E. marmotae and only between 7,268 and 7,280 in E. coli, with no overlap (p < 0.001). Application of these spectral criteria to 176 clinical isolates revealed the first identification of a E. marmotae isolate from a human infection in North America. The isolate had originally been diagnosed as E. coli based on a 99.1% IVD confidence score. This first North American clinical isolate was confirmed as E. marmotae by Taqman-PCR and whole genome sequencing. This isolate had numerous antibiotic resistance gene markers and unlike most clinical E. coli, this E. marmotae isolate lacked motility at 37°C.ConclusionClinical tests based on these methods of differentiating E. marmotae and E. coli may assist in determining the prevalence of this emerging pathogen and making therapeutic decisions.